Pulse Pressure: An Emerging Therapeutic Target for Dementia - Levin, Rachel A.; Carnegie, Mark H.; Celermajer, David S. (Frontiers in Neuroscience, 2020)
Elevated pulse pressure can cause blood brain barrier dysfunction and subsequent adverse neurological changes that may drive or contribute to the development of dementia with age. In short, elevated pulse pressure dysregulates cerebral endothelial cells and increases cellular production of oxidative and inflammatory molecules. The resulting cerebral microvascular damage, along with excessive pulsatile mechanical force, can induce breakdown of the blood brain barrier, which in turn triggers brain cell impairment and death. We speculate that elevated pulse pressure may also reduce the efficacy of other therapeutic strategies for dementia. For instance, BACE1 inhibitors and anti-amyloid-β biologics reduce amyloid-β deposits in the brain that are thought to be a cause of Alzheimer’s disease, the most prevalent form of dementia. However, upregulation of oxidative and inflammatory molecules and increased amyloid-β secretion by cerebral endothelial cells exposed to elevated pulse pressure may hinder cognitive improvements with these drugs. Additionally, stem or progenitor cell therapy has the potential to repair blood brain barrier damage, but chronic oxidative and inflammatory stress due to elevated pulse pressure can inhibit stem and progenitor cell regeneration. Finally, we discuss current efforts to repurpose blood pressure medications to prevent or treat dementia. We propose that new drugs or devices should be developed to safely reduce elevated pulse pressure specifically to the brain. Such novel technologies may alleviate an entire downstream pathway of cellular dysfunction, oxidation, inflammation, and amyloidogenesis; thereby preventing pulse-pressure-induced cognitive decline. Furthermore, these technologies may also enhance efficacy of other dementia therapeutics when used in combination.